The modernization of Krueng Geukuh port in supporting the special economic zones (Sez) Of Arun Lhokseumawe, Indonesia - Zulkarnaen, Iskandar; Saputra, Jumadil; Fauzi, .; Suzanna, Ella; Rahmawati, . (Opción, 2019)
The seaport plays an important role as a vital area beside sea transportation for local, regional, national and international economic, social development and even social changes. Krueng Geukeuh seaport is one of the biggest ports in Lhokseumawe city that can accelerate the economic growth of Lhokseumawe. Of the goal of this study is collecting data from several sources and analyzing using contents analysis. The result of the study indicates that the problem why this port cannot carry out its functions properly is government policies.